Piperine-loaded solid lipid nanoparticles: a promising nano-phytomedicine for the treatment of non-alcoholic fatty liver disease - Moin, Afrasim; Ram, Shwetha; Boregowda, Sateesha Shivally; Hussain, Talib; Abu Lila, Amr Selim; Jayaramu, Rajamma Abburu; Rizvi, Syed Mohd Danish; Anwar, Sirajudheen; Chandan, Kalegowda (Frontiers in Pharmacology, 2026)
IntroductionPiperine (PIP), the active alkaloid found in black pepper (Piper nigrum), has gained attention for its potential therapeutic role in managing non-alcoholic fatty liver disease (NAFLD) due to its anti-inflammatory, lipid-lowering, antioxidant, and insulin-sensitising properties. Nevertheless, PIP’s poor solubility limits its absorption in the gastrointestinal tract, thereby, compromising its systemic bioavailability. Consequently, the objective of this research has been to formulate piperine-loaded solid lipid nanoparticles (PIP- SLNs) so as to increase its oral bioavailability and prolong its hepatic circulation time.MethodsHerein, PIP-SLNs were prepared by the hot homogenization method. The fabricated PIP-SLNs were characterized for size, zeta potential, surface morphology, entrapment efficiency and in vitro release performance. The impact of the optimized formula (F6) on key parameters associated with NAFLD, such as oral glucose tolerance (OGTT), aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol (TC), triglyceride (TG) levels, and liver weight, was evaluated using a hyperlipidaemic Swiss albino mice model. Additionally, liver histopathology was examined pre- and post-treatment to assess the efficacy of PIP-SLNs in mitigating hyperlipidaemia.Results and discussionParticle size, zeta potential, and drug entrapment efficiency of the optimized formula (F6) was found to be 191.2 ± 27.9 nm, - 20 ± 1.3 mV, 72.3% ± 2.8, respectively. Morphologically, the PIP-SLNs were found to be spherical. The optimized formulation (F6) exhibited sustained release up to 70% at 48 h, fitting the Higuchi model (R2 = 0.976) indicative of diffusion-driven release, with a Korsmeyer‐Peppas exponent (n = 0.63), further confirming anomalous diffusion-relaxation transport. Most importantly, the NAFLD study demonstrated a significant (p < 0.05) drop in blood glucose levels, serum markers (AST and ALT, p < 0.001), total cholesterol and triglycerides (p < 0.05), and also liver weight (p < 0.028), which was far superior to those elicited by plain PIP suspension. These findings reiterate the potential of solid lipid nanoparticles in increasing the bioavailability and thereby its hepatic circulation of PIP, which in turn, significantly enhanced its hepatoprotective effect in NAFLD.